A Comparative Study of Women’s Leadership in Family Businesses: Insights from Indonesia and Thailand - Nanda Fathiyah Gumay; Mira Rozanna (goodwood publishing, 2026)
Purpose: This study compares women’s leadership in family businesses in Indonesia and Thailand, focusing on succession dynamics, board diversity, cultural norms, and institutional support. This study aims to understand how cultural and institutional contexts shape women’s opportunities to assume leadership roles in family enterprises. Research Methodology: A qualitative comparative analysis was conducted using secondary data from Scopus- and SINTA-indexed journals, regional surveys, and institutional reports. The analysis applied a thematic framework informed by role congruity theory, resource-based view, Hofstede’s cultural dimensions, and institutional theory, with data triangulation ensuring credibility. Results: Indonesian family firms are strongly influenced by patriarchal norms, informal succession, and weak institutional support, which limits women’s leadership. In Thailand, succession is more formalized, institutional support is stronger, and women’s visibility in governance is greater. However, in both countries, women’s representation does not always ensure their authority. Conclusions: This study concludes that women’s leadership is shaped less by capability than by governance practices and institutional frameworks. Thailand provides a more enabling context, whereas Indonesia reflects stronger cultural resistance. Limitations: This study is limited by its reliance on secondary data and its focus on only two countries. Contributions: This research enriches management, gender studies, and entrepreneurship by offering Southeast Asian comparative insights and practical implications for policymakers and family-business leaders.